The Unrevealed Truth about the Tongue in Forensic Identification - Savla S; Gotmare S; Pereira T; Waghmare. M; Shetty S; Kamath P; Shah T (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Forensic odontology, a branch of dentistry includes identification of individuals in variouscrime scenes, natural calamities, and mass disasters. The identification is possible because every individualbody is unique and so is our tongue due to its morphological variations. The primary objective of the studywas to assess the morphological features of the tongue and its use in sex determination.Methods: The study included a sample size of 100 individuals (50 males and 50 females) in the age rangeof 20-50 years old. Photographs were taken of front and side view of the tongue; visual inspection wasdone and lastly impressions of the tongue were made with help of alginate and then poured with the helpof dental stone. IBM SPSS statistics 20.0 (IBM Corporation, Armonk, NY, USA) was used for the analysesof the data. Microsoft word and Excel were used to generate graphs, tables etc. Females presented withtriangular shape, presence of shallow fissures more commonly and a sharp lingual apex of tongue. Malespresented with rectangular shape, presence of deep fissure/absence of fissures more commonly and septate/sharp lingual apex of the tongue.Conclusion: Tongue exhibits various unique characteristics and can be used in sex determination.